Influence of Chromium-Cobalt-Molybdenum Alloy (ASTM F75) on Bone Ingrowth in an Experimental Animal Model - Zuchuat, Jésica Itatí (2017)
Cr-Co-Mo (ASTM F75) alloy has been used in the medical environment, but its use as a rigid barrier membrane for supporting bone augmentation therapies has not been extensively investigated. In the present study, Cr-Co-Mo membranes of different heights were placed in New Zealand white, male rabbit tibiae to assess the quality and volume of new bone formation, without the use of additional factors. Animals were euthanized at 20, 30, 40, and 60 days. Bone formation was observed in all of the cases, although the tibiae implanted with the standard membranes reached an augmentation of bone volume that agreed with the density values over the timecourse. In all cases, plasmatic exudate was found under the membrane and in contact with the new bone. Histological analysis indicated the presence of a large number of chondroblasts adjacent to the inner membrane surface in the first stages, and osteoblasts and osteocytes were observed under them. The bone formation was appositional. The Cr-Co-Mo alloy provides a scaffold with an adequate microenvironment for vertical bone volume augmentation, and the physical dimensions and disposition of the membrane itself influence the new bone formation.